2018
DOI: 10.1111/1365-2664.13124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation management intensity on biodiversity and ecosystem services in vineyards: A meta‐analysis

Abstract: At the global scale, vineyards are usually managed intensively to optimize wine production without considering possible negative impacts on biodiversity and ecosystem services (ES) such as high soil erosion rates, degradation of soil fertility or contamination of groundwater. Winegrowers regulate competition for water and nutrients between the vines and inter‐row vegetation by tilling, mulching and/or herbicide application. Strategies for more sustainable viticulture recommend maintaining vegetation cover in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
136
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 191 publications
(144 citation statements)
references
References 73 publications
4
136
1
3
Order By: Relevance
“…Beyond the type of farming systems, specific farming practices such as pesticide use intensity, tillage intensity, and crop productivity are key factors impacting natural enemy abundance and species richness. Our results clearly highlight that reducing management intensity at the field scale is beneficial for natural enemy abundance and diversity (Winter et al, ). Field age was also a strong factor explaining natural enemy richness.…”
Section: Discussionsupporting
confidence: 64%
“…Beyond the type of farming systems, specific farming practices such as pesticide use intensity, tillage intensity, and crop productivity are key factors impacting natural enemy abundance and species richness. Our results clearly highlight that reducing management intensity at the field scale is beneficial for natural enemy abundance and diversity (Winter et al, ). Field age was also a strong factor explaining natural enemy richness.…”
Section: Discussionsupporting
confidence: 64%
“…The strong positive effect of extensive vegetation management agrees with other studies reporting the benefits of extensive agricultural management practices for wild bees in different crop systems (Nicholson et al, ; Shuler, Roulston, & Farris, ), as well as vineyards (Kehinde & Samways, , , ). Moreover, a recent meta‐analysis confirmed that positive affect of extensive management on overall biodiversity and ecosystem services (Winter et al, ). Ground‐nesting bees benefit from undisturbed soil conditions and can utilize vineyard inter‐rows as nesting habitat.…”
Section: Discussionmentioning
confidence: 84%
“…The implementation of pollinator‐friendly management ultimately benefits other ecosystem services like for example soil erosion mitigation, surface water runoff reduction, or biological pest control as well as biodiversity conservation (Wratten et al, ). Many of those ecosystem services are relevant for winegrowers and positively affected by extensive inter‐row management intensities in vineyards (Winter et al, ). For example, extensive vegetation management significantly improves soil loss mitigation (Winter et al, ), which is highly relevant in vineyards that are situated on hilly terrain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations